Strategi Personal Branding Guru Bimbingan dan Konseling dalam Meningkatkan Minat Siswa Mengakses Layanan Konseling Studi Kasus di SMPN 14 Denpasar - Komang Ugrasena; I Wayan Wastawa (Fakultas Dharma Duta, 2026)
This study aims to analyze the personal branding strategies of guidance and counseling (GC) teachers in building trust and increasing students’ interest in accessing counseling services at SMP Negeri 14 Denpasar. This study employed a qualitative approach with a case study design. Data were obtained through observation, in-depth interviews, and documentation involving GC teachers and students who were purposively selected. The data were analyzed interactively through data condensation, data presentation, and conclusion drawing and verification. Data validity was ensured through source and technique triangulation, member checking, and an audit trail. The results showed that the personal branding of GC teachers was implicitly built through communication that was friendly, open, empathetic, responsive, and consistent, and was strengthened through the use of digital media as a space for delivering information and initiating communication with students. Trust was an important element linking personal branding to students’ interest in accessing counseling services. Positive experiences with GC teachers can reduce psychological distance and encourage students to seek assistance voluntarily. However, this strategy did not generate uniform responses because some students continued to perceive counseling services as being associated with disciplinary violations and punishment. These findings confirm that the personal branding of GC teachers is a long-term communication process that requires consistency, authenticity, service quality, and digital adaptation to build trust and increase students’ access to counseling services